Mobile ad hoc network integrated wireless networks: a survey - S.SivaNageswara Rao, Dr; Aruna, Orchu; K.Lakshminadh, Dr (International Journal of Engineering and Technology, 2018)
Now a day, every one using mobile devices for communicating with others. The development of new technologies, like Internet of Things (IoT) needs coverage, connectivity, scalability and QoS. In ubiquity networks, the major issues are coverage, connectivity, scalability and QoS. To solve these limitations, integrating wireless networks with ad hoc networks. This paper provides detail survey on how ad hoc networks are integrated with Cellular Network, Wireless Mesh Networks and Wireless Sensor Networks. This integration may resolve the problems of coverage, connectivity, scalability and QoS.